A critical (and interdisciplinary) survey of popular music genre theories - Merlini, Mattia (Interdisciplinary Studies in Musicology, 2020)
Genres are among the most discussed topics in popular music studies. The attempt to explain issues as complex and layered as how musical genres are born, how they work and what they ontologically are cannot avoid opening a box full of theoretical problems, questions and tools that need to be understood and used in order to say something significant on genre today. Despite the long story of this theoretical debate (roots of which can be traced back to ancient Greece) and the variety of disciplines involved (e.g. literature, music and film studies, but also philosophy, sociology, cultural studies and semiotics), it is difficult to find survey papers that can give an overview of such a rich research environment. This paper attempts to fill that void by trying to systematize the main (contemporary) perspectives on musical genre, in particular non-essentialist theories coming from the overlapping fields of musicology and sociology. Most importantly, its overview stresses the necessity of an interdisciplinary study of musical genre, which – as an exemplum of extraordinarily layered phenomenon of the human production of culture – intertwines technical, social, discursive, commercial, historical and other elements, thus requiring an approach capable of accounting for as much of its many layers of meaning as possible.